2013
DOI: 10.1016/j.chom.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A Receptor-like Cytoplasmic Kinase Targeted by a Plant Pathogen Effector Is Directly Phosphorylated by the Chitin Receptor and Mediates Rice Immunity

Abstract: CERK1 is a lysine motif-containing plant pattern recognition receptor for chitin and peptidoglycan. Chitin recognition by OsCERK1 triggers rapid engagement of a rice MAP kinase cascade, which leads to defense response activation. How the MAP kinase cascades are engaged downstream of OsCERK1 remains obscure. Searching for host proteins that interact with Xoo1488, an effector of the rice pathogen Xanthomonas oryzae, we identified the rice receptor-like cytoplasmic kinase, OsRLCK185. Silencing OsRLCK185 suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
266
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(272 citation statements)
references
References 34 publications
6
266
0
Order By: Relevance
“…1A). Then, by quantitative reverse transcription (qRT)-PCR, we examined the expression of five defense-related genes, Oryza sativa pathogenesisrelated protein1 (OsPR1), OsPR10, and the PTI-related genes Oryza sativa probenazole-inducible1, OsKS4, and OsNAC4 (Park et al, 2012;Yamaguchi et al, 2013). The transcripts of all five genes were significantly increased in IRBLkm-Ts and IRBLz5-CA in comparison with those in LTH (Fig.…”
Section: Identification Of the Monogenic Resistant Line With Strong Dmentioning
confidence: 99%
“…1A). Then, by quantitative reverse transcription (qRT)-PCR, we examined the expression of five defense-related genes, Oryza sativa pathogenesisrelated protein1 (OsPR1), OsPR10, and the PTI-related genes Oryza sativa probenazole-inducible1, OsKS4, and OsNAC4 (Park et al, 2012;Yamaguchi et al, 2013). The transcripts of all five genes were significantly increased in IRBLkm-Ts and IRBLz5-CA in comparison with those in LTH (Fig.…”
Section: Identification Of the Monogenic Resistant Line With Strong Dmentioning
confidence: 99%
“…In addition to Pto and PBS1, RLCKs such as BIK1, PBL1, RIPK, and OsRLCK185 are also targeted by pathogen effector proteins (J. Liu et al, 2011;Feng et al, 2012;Yamaguchi et al, 2013), further supporting the importance of RLCKs in plant immunity.…”
mentioning
confidence: 94%
“…Another RLCK, BSK1, also interacts with FLS2 and is required for flagellin-induced ROS production (Shi et al, 2013). In rice (Oryza sativa), the RLCK OsRLCK185 associates with OsCERK1 (Yamaguchi et al, 2013). It is phosphorylated by OsCERK1 after chitin treatment and is required for chitin-induced immune responses.…”
mentioning
confidence: 99%
“…OsRLCK185 indicate that phosphorylation of a cluster of Ser and Thr residues residing within the kinase activation loop are necessary for RLCK activity (Lu et al, 2010;Zhang et al, 2010;Yamaguchi et al, 2013;Ao et al, 2014). These phosphorylated residues are highly conserved among RLCK VII members Yamaguchi et al, 2013;Ao et al, 2014).…”
Section: Pbl13 Autophosphorylation Primarily Localizes To Its C-termimentioning
confidence: 99%
“…Analysis of BIK1 paralogs revealed that AvrPphB SUSCEPTIBLE1 (PBS1) and AvrPphB SUSCEPTIBLE1-LIKE1 (PBL1) function additively with BIK1 to regulate the ROS burst . RLCKs in subfamily VII have also been shown to be important for perception of chitin, a fungal MAMP Yamaguchi et al, 2013;Ao et al, 2014;Shinya et al, 2014). Rice (Oryza sativa) RLCK185, OsRLCK176, and Arabidopsis (Arabidopsis thaliana) PBL27 were also found to associate with the chitin coreceptor, indicating that RLCKs represent an important signaling module downstream of multiple PRR complexes (Yamaguchi et al, 2013;Ao et al, 2014;Shinya et al, 2014).…”
mentioning
confidence: 99%